Therapeutic efficacy of acupuncture point stimulation for stomach cancer pain: a systematic review and meta-analysis - Zhou, Xuancheng; Zhang, Jieying; Jiang, Lai; Zhang, Shengke; Gu, Yuheng; Tang, Jingyi; Pu, Tong; Quan, Xiaomin; Chi, Hao; Huang, Shangke (Frontiers in Neurology, 2024)
Purpose In recent years, traditional Chinese medicine has received widespread attention in the field of cancer pain treatment. This meta-analysis is the first to evaluate the effectiveness and safety of acupuncture point stimulation in the treatment of stomach cancer pain. Methods For this systematic review and meta-analysis, we searched PubMed, Web of Science, Cochrane Library, Embase, WANFANG, China National Knowledge Infrastructure (CNKI), and Chinese Journal of Science and Technology (VIP) databases as well as forward and backward citations to studies published between database creation to July 27, 2023. All randomized controlled trials (RCTs) on acupuncture point stimulation for the treatment of patients with stomach cancer pain were included without language restrictions. We assessed all outcome indicators of the included trials. The evidence from the randomized controlled trials was synthesized as the standardized mean difference (SMD) of symptom change. The quality of the evidence was assessed using the Cochrane Risk of Bias tool. This study is registered on PROSPERO under the number CRD42023457341. Results Eleven RCTs were included. The study included 768 patients, split into 2 groups: acupuncture point stimulation treatment group (n = 406), medication control group (n = 372). The results showed that treatment was more effective in the acupuncture point stimulation treatment group than in the medication control group (efficacy rate, RR = 1.63, 95% CI 1.37 to 1.94, p < 0.00001), decreasing in NRS score was greater in acupuncture point stimulation treatment group than in the medication control group (SMD = −1.30, 95% CI −1.96 to −0.63, p < 0.001). Systematic Review Registration https://clinicaltrials.gov/, identifier CRD42023457341.